PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MODEL MISSOURI MATHEMATICS PROJECT(MMP) BERBANTUAN MEDIA PEMBELAJARAN E-LEARNING MOODLE PADAPOKOK BAHASAN FUNGSI KOMPOSISI DAN FUNGSI INVERS KELAS XI IPS SEMESTER GENAPTAHUNAJARAN2012/2013 - Athoillah, M. Wildan; Dafik, D; Hobri, H (Kadikma, 2013)
Abstract.The use of ICT in Indonesianeducation especially in the field of mathematics is less optimal. It would require the development of materials that use e-learning to facilitate students in learning. The device was developed by a model of learning missourimathematics project (MMP). The developments of material methods are using the method of Thiagarajan, Semmel and Semmel. Based on the results of the expert appraisal, validity coefficient of lesson plans,worksheets,student books, THB and e-learning in a row is 0.94; 0.96; 0.90; 0.93 and 0.92 which means the device is already valid. Observations of teachers in managing the learning ability, the percentage of student activity, student questionnaire responses, student self-assessment questionnaires and tests learning outcomes showed that the device is practical and effective. Key Words :Missouri Mathematics Project,Learning device, E-learning, Moodle.